Four new species of Gallerucida Motschulsky, 1861 from China (Coleoptera: Chrysomelidae: Galerucinae) - Xu, Si-Yuan; Yang, Xing-Ke (Zootaxa, 2024)
Four new species of the genus Gallerucida Motschulsky, 1861 from China, G. mantillerii sp. nov. distributed in Guangxi and Guizhou, G. rubicornis sp. nov. distributed in Henan, Hunan, Hubei, Fujian and Guizhou, G. rubiginosa sp. nov. distributed in Xizang, and G. rubrimelaena sp. nov. distributed in Guangxi, Guizhou and Yunnan, are described, with their habitus and major diagnostic features illustrated.